Human influence on bottlenose dolphin (Tursiops truncatus) strandings in the northern Gulf of Mexico - Carmichael, Ruth H.; Hodanbosi, Matthew R.; Russell, Mackenzie L.; Wingers, Noel L. (Frontiers in Environmental Science, 2022)
Human activity affects marine mammal stranding rates in two major ways; through human interaction (HI) that may lead to mortality and through search and response efforts that enable carcass detection. To better quantify the combined effects of these interacting human influences, we analyzed strandings for common bottlenose dolphin (Tursiops truncatus) in the northern Gulf of Mexico (nGOM), an area of high cetacean strandings. To identify hotspots of human influence, we first determined the number of total and HI-related bottlenose dolphin strandings normalized to shoreline length in each nGOM U.S. state, which represent major response areas. To estimate the effects of response effort on stranding number (for HI and non-HI strandings), we used the Deepwater Horizon oil spill (DWHOS) as an established benchmark to compare periods of lower (pre-spill) and higher (post-spill) response effort. Strandings in Alabama waters were used as a case study to detail spatial and temporal variation due to human influences during the 39-year period of retrospective study. We found an increase in strandings from Louisiana through Alabama following the DWHOS. Non-oil related HI strandings increased in total number in AL, and they increased as a proportion of total strandings in Alabama (16%) and the Florida panhandle (12%). The increase in HI-related strandings in Alabama was driven by mortality of many types, but particularly fishery interactions and cases of apparent intentional harm. The Alabama case study clearly detected lower stranding numbers during periods of low or intermittent response coverage. Our findings are consistent with an overall increase in stranding numbers due to a combination of increased stranding occurrence and response effort following the DWHOS. Importantly, we provide evidence that HI-related standings increased independently from the DWHOS, with ongoing increases in at least one hotspot (Alabama). These findings provide a first step to parsing out different effects of human influences on stranding data for a common coastal cetacean. Our approach establishes baselines for future damage and recovery assessments, identifies areas where resources can be focused for management and education, and highlights the power of response and monitoring agencies to positively influence stranding datasets.